Introvert Learners’ Need Analysis of English-Speaking Activity - Dinda Amalia; Nida Husna (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThe objective of this research was to reveal the introvert learner’s necessities, lacks, wants and learning needs in English speaking activity. This research was conducted at three state Islamic junior high schools in South Jakarta in order to solve the introvert learners’ problems deals with self-confidence and social interaction in English speaking activity. It was presented in a mixed-method research and used the explanatory sequential strategy. The participants in this research were 106 introvert learners on the eighth grade for quantitative data meanwhile nine introvert learners and four English teachers for qualitative data. The data of the study were collected through questionnaire and interview. The quantitative data were analysed using simple descriptive statistic while the qualitative data were analysed using Creswell’s theory. The study showed that introvert learners learn English speaking skill in order to communicate properly in English and facilitate their learning in other skills. Since the difficult learning material and the lack of vocabulary were the main obstacles for introvert learners, the English teacher can give them keywords and examples, then teach based on their interest in speaking activity to support the learning process. In this regard, the introvert learners like to discuss dialogues and experience topics by pairs, watching English movies, and listening to English songs. By identifying the necessities, lacks, wants, and learning needs, the teacher can facilitate the learning process through a friendly atmosphere.ABSTRAKPenelitian ini bertujuan untuk mengungkapkan tujuan, kekurangan, minat, dan kebutuhan belajar siswa introvert dalam aktivitas berbahasa Inggris. Penelitian ini dilasanakan di tiga MTs Negeri di Jakarta Selatan dengan tujuan untuk menyelesaikan masalah siswa introvert terkait kepercayaan diri dan interaksi sosial dalam kegiatan berbahasa Inggris. Penelitian ini disajikan dalam penelitian metode campuran dan menggunakan strategi sekuensial penjelasan. Peserta dari penelitian ini adalah 106 siswa introvert di kelas delapan untuk data kuantitatif dan sembilan perwakilan siswa introvert dan empat guru bahasa Inggris untuk data kualitatif. Data penelitian dikumpulkan melalui angket dan wawancara. Data kuantitatif dianalisis menggunakan statistik deskriptif sederhana sedangkan data kualitatif dianalisis menggunakan teori Creswell. Studi ini mengungkapkan bahwa siswa introvert mempelajari keterampilan berbahasa Inggris untuk berkomunikasi dengan baik dalam bahasa Inggris dan memfasilitasi pembelajaran mereka di kemampuan lainnya. Karena materi pembelajaran yang sulit dan kurangnya kosa kata adalah hambatan utama bagi siswa introvert, guru bahasa Inggris dapat memberi mereka kata kunci dan contoh, kemudian mengajar berdasarkan minat mereka dalam kegiatan berbicara untuk mendukung proses pembelajaran. Dalam hal ini, siswa introvert suka mendiskusikan dialog dan topik pengalaman secara berpasangan, menonton film berbahasa Inggris, dan mendengarkan lagu-lagu bahasa Inggris. Dengan mengidentifikasi kebutuhan, kekurangan, minat, dan kebutuhan belajar, guru dapat memfasilitasi proses pembelajaran melalui suasana yang bersahabat. How to Cite: Amalia, D., Husna, N. (2019). Introvert Learners’ Need Analysis of English-Speaking Activity. IJEE (Indonesian Journal of English Education), 6(2), 91-108. doi:10.15408/ijee.v6i2.15466